2020
DOI: 10.1016/j.wneu.2019.10.157
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Moyamoya Presenting as a Subarachnoid Hemorrhage from a Ruptured Anterior Cerebral Artery Aneurysm

Abstract: Background: The incidence of Moyamoya disease (MMD)-associated intracranial aneurysms ranges from 3% to 14% in adult patients, whereas this complication has been rarely reported in children. Case Description: We herein report the first case of an extremely rare subarachnoid hemorrhage (SAH) presentation of a child with a ruptured anterior cerebral artery (ACA) dissecting aneurysm secondary to a newly discovered, unilateral Moyamoya-like pathology. Conclusion: MMD-associated aneurysms are extremely rare in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Noureldine et al reported the case of a 14year-old girl exhibiting subarachnoid hemorrhage due to a ruptured ACA aneurysm associated with MMD. 10 The nature of the aneurysm, however, seemed to differ from that of the present case because the aneurysm was located at the A1 portion, and a dissecting aneurysm was suspected. Within their case series of MMDassociated aneurysms, Liu et al reported a 9-year-old boy with an unruptured ACoA aneurysm.…”
Section: Observationscontrasting
confidence: 65%
“…Noureldine et al reported the case of a 14year-old girl exhibiting subarachnoid hemorrhage due to a ruptured ACA aneurysm associated with MMD. 10 The nature of the aneurysm, however, seemed to differ from that of the present case because the aneurysm was located at the A1 portion, and a dissecting aneurysm was suspected. Within their case series of MMDassociated aneurysms, Liu et al reported a 9-year-old boy with an unruptured ACoA aneurysm.…”
Section: Observationscontrasting
confidence: 65%
“…Table 1 summarizes our patient and 2 others with surgically treated MMD-related ACA aneurysms who were described in previous reports. 11 , 12 Two presented with aneurysm rupture and intracranial hemorrhage. One had bilateral MMD.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical clipping of MMD-related cerebral aneurysms is difficult because moyamoya vessels generally obstruct the approach, and these vessels are easily damaged because of their fragility. 11 Although endovascular embolization of a true aneurysm can achieve a good result, 12 embolizing a pseudoaneurysm may result in rehemorrhage and regrowth. In our patient, we elected to perform both STA-MCA and STA-ACA target bypass to reduce the hemodynamic stress on the left ACA.…”
Section: Discussionmentioning
confidence: 99%
“…These authors argued that prompt intervention is essential to exclude the risk of the ruptured aneurysmrebleeding due to persistent hemodynamic stress. [51]. Reports on patients with pMMD who present cerebral ischemic complications after intraventricular haemorrhage (IVH) and/or intracerebral bleeding (ICB) are minimal.…”
Section: Pediatric Moyamoya Disease (Pmmd)mentioning
confidence: 99%